2019
DOI: 10.1103/physrevaccelbeams.22.041002
|View full text |Cite
|
Sign up to set email alerts
|

Stability modeling of the LHC Nb-Ti Rutherford cables subjected to beam losses

Abstract: The Large Hadron Collider (LHC) at CERN is being prepared for its full energy exploitation during run III, i.e., an increase of the beam energy beyond the present 6.5 TeV, targeting the maximum discovery potential attainable. This requires an increase of the operating field of the superconducting dipole and quadrupole magnets, which in turn will result in more demanding working conditions due to a reduction of the operating margin while the energy deposited by particle loss will increase. Beam-induced magnet q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The model was benchmarked against experimental values of the LHC quench limits reconstructed from the machine operation quenches at 6.5 TeV of beam energy for the MB (Main Bending) dipole magnets [38]. The model was able to reproduce the experimental results over a wide range of heat deposition times (as shown in Section IV.B), and was therefore applied to compare different beam energies and to the analysis of the LHC Main Quadrupole [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model was benchmarked against experimental values of the LHC quench limits reconstructed from the machine operation quenches at 6.5 TeV of beam energy for the MB (Main Bending) dipole magnets [38]. The model was able to reproduce the experimental results over a wide range of heat deposition times (as shown in Section IV.B), and was therefore applied to compare different beam energies and to the analysis of the LHC Main Quadrupole [41].…”
Section: Resultsmentioning
confidence: 99%
“…Fig. 7 also reports quench and no-quench energy data points reconstructed from the LHC machine operation in the three years from 2016 to 2018, as explained in detail in [41].…”
Section: B Physical Parametersmentioning
confidence: 99%
“…Comparing the distributions for the two upper intensity intervals, the characteristics of dust particle events are not expected to get significantly worse in the HL-LHC era. The minimum energy deposition density for inducing a quench decreases for shorter heating times, but this decrease is small for τ < 10 −4 s [48,51]. The shift of the τ distribution is therefore not expected to considerably increase the risk of quenches.…”
Section: Proton Losses At Higher Beam Intensitiesmentioning
confidence: 96%
“…Results are not directly linked or linkable to quench sources though. On a small time-scale which is more relevant for fundamental research, detailed models provide a good basis for process description, even on a grand magnet scale [4], [11], [33]. While available software proves to be invaluable for magnet design and performance analysis, we still need to try distinguishing quench cases where multi-physics software can be tested in more complex conditions.…”
Section: Quench Sourcementioning
confidence: 99%
“…It also takes place during quenching and can serve as an indicator of it and possibly as a precursor of it. While the physics of current redistribution is clear and various related processes studied [4[, [5], [12], [32], [33], [34] a significant complication for interpretation in real magnets is the existence of splices (review on splice/joint technology for various superconductors can be found in [35]). Lead splices can be considered in approximation of equal potential for all strands or equal current in all strands with the two giving very different current/power loss distribution outcomes [4].…”
Section: Current Redistributionmentioning
confidence: 99%